(untitled) - John Dixon (Rome, Italy, 2001)
Through an examination of a wide variety of farming systems across the developing world, this book shows how the farming systems approach can be used to identify key local, regional and international priorities for the reduction of hunger and poverty. It examines the various strategies open to poor farm families seeking better lives, and shows how such strategies differ in relative importance from one farming system to another. Fainally, the book discusses how an effective response to these priorities and strategies will require a rethinking of the roles of key stakeholders in the development process - farmers themselves, their communities, civil society, governemts and the international community.
Keywords: agricultural systems,agriculture,agriculture; innovations,technology transfer